The Effect Of Freshwater Lobster Stock Development (Cherax Quadricarinatus) On Sustainability And Growth With Recirculation Systems - Andriyeni Andriyeni; Zulkhasyni Zulkhasyni; Citra Dwi Ayu Lestari; Dedi Pardiansyah; Yulfiperius Yulfiperius (University of Prof. Dr. Hazairin, SH, 2022)
This study aims to determine the effect of different stocking densities on the survival of crayfish (Cherax quadricarinatus). The design used in this study was a completely randomized design (CRD) consisting of five trials, namely experiment 1 (stocking density of 8 individuals/container), experiment 2 (stocking density of 9 individuals/container), experiment 3 (stocking density of 10 individuals/container). experimental container 4 (stocking density of 11 individuals/container), experiment 5 (stocking density of 12 individuals/container) with four replications.The parameters observed were survival, growth length, crayfish weight, feed conversion and feed efficiency.The experimental results showed that the effect of stocking density on the survival and growth of crayfish (Cherax quadricarinatus) had a very significant effect on the parameters of survival, feed conversion and feed efficiency but had no effect on the length and weight of the crawfish shrimp.The best experiment was at a stocking density of 8 individuals and 10 fish which had a survival rate of 87.50%.The best feed conversion and feed efficiency were found at the stocking density of 10 fish, namely 4.58 and e feed efficiency is 22.02%.